Characterisation of erythropoietin gene-modified human mesenchymal stem cells and anti-apoptotic effect of glutamate excitotoxicity in a retinal neuron cell line - Shirley, Ding Suet Lee (2017)
Retinal degeneration is a prominent feature in ocular disorders. In exploring possible treatments, Mesenchymal Stem Cells (MSCs) have been recognised to yield therapeutic role for retinal degenerative diseases. Studies have also shown that erythropoietin (EPO) administration into degenerative retina models confers significant neuroprotective actions in limiting pathological cell death. For this reason, introducing anti-apoptotic proteins, such as erythropoietin (EPO), may exhibit a superior effect in enhancing beneficial activity of MSCs and hence, the treatment in retinal degenerative disorders. The objective of this study was to characterise EPO gene-modified human MSCs and evaluate its anti-apoptotic effect of glutamate excitotoxicity in a retinal neuron cell line. MSCs derived from the human Wharton’s jelly of umbilical cord were cultured, expanded, and characterised for immunophenotypical expression of MSC surface markers and multipotency differentiation potentials. Following that, MSCs were genetically modified to carry EPO through lentiviral transduction. The cells were transduced with lentivirus particles encoding EPO and green fluorescent protein (GFP), as a reporter gene. The cultured MSCs displayed plastic adherence properties and formed spindle-shaped cells that resembled a fibroblast. MSC immunophenotyping revealed high expression of CD90, CD73 (SH3), CD105 (SH2), CD29, and HLA-ABC but lack of expression for CD34, CD14, CD45, CD80, and CD86. Furthermore, MSCs were capable to undergo bilineage mesenchymal differentiation into adipocytes and osteocytes. EPO-expressing MSCs (MSC-EPO) also demonstrated a greater capacity to promote cell differentiation into nestin-expressing neurospheres when compared to non-transduced cells. The supernatants of the transduced and non-transduced cells were collected and used as a pre-conditioning medium for Y79 retinoblastoma cells (retinal neuron cell line), following exposure to glutamate treatment to induce apoptosis. Cellular recovery of human retinoblastoma (Y79) subjected to glutamate at a toxic dose was assessed following incubation with supernatants harvested from EPO transduced MSCs. Retinal cells exposed to glutamate showed enhanced improvement in cell viability and reduced mitochondrial depolarization when incubated with the preconditioned medium collected from EPO-transduced cells. The outcome of this study established a proof-of-concept that MSCs could be used as a candidate for the delivery of EPO therapeutic gene in the treatment of retinal degenerations and that generated MSC-EPO can further differentiate into neural lineage that may serve as an alternative for cell replacement therapy for degenerating retinal neurons.